Improving the understanding and management of back pain in older adults: the BOOST research programme including RCT and OPAL cohort - Esther Williamson; Maria T Sanchez-Santos; Ioana R Marian; Mandy Maredza; Cynthia Srikesavan; Angela Garrett; Alana Morris; Graham Boniface; Susan J Dutton; Frances Griffiths; Gary S Collins; Stavros Petrou; et al. (NIHR Journals Library, 2023)
Background Back pain frequently affects older people. Knowledge about back pain in older people and evidence to inform clinical care was lacking, particularly for older people with neurogenic claudication due to spinal stenosis, which is a debilitating condition. Objectives To understand and reduce the burden of back pain on older people by increasing knowledge about back pain in older people and developing evidence-based treatment strategies. Design We completed six work packages. These were not undertaken chronologically as there was overlap between work packages. Work package 1: Refine a physiotherapy intervention for neurogenic claudication. Work package 2: Feasibility of the Oxford Pain Activity and Lifestyle cohort study and Better Outcomes for Older people with Spinal Trouble randomised controlled trial. Work package 3: Development of a prognostic tool to identify when older people are at risk of mobility decline using data from the Oxford Pain Activity and Lifestyle cohort study. Work package 4: A randomised controlled trial of physiotherapy for neurogenic claudication and nested longitudinal qualitative study (Better Outcomes for Older people with Spinal Trouble randomised controlled trial). Work package 5: Predictors of participants' response to treatment - prespecified subgroup analyses. Work package 6: Implementation planning. Setting Primary care and National Health Service Community and Secondary Care Trusts. Participants Community-dwelling adults over the age of 65 years and registered with primary care practices. Better Outcomes for Older people with Spinal Trouble trial participants reported back and/or leg pain consistent with neurogenic claudication. Interventions The Better Outcomes for Older people with Spinal Trouble programme was a physiotherapy-delivered combined physical and psychological group intervention for older people with neurogenic claudication. The comparator was a physiotherapy assessment and tailored advice (best practice advice). Main outcome measures The primary outcome for the Oxford Pain Activity and Lifestyle prognostic tool was mobility decline based on the EQ-5D-5L Mobility Question. The primary outcome for the Better Outcomes for Older people with Spinal Trouble trial was the Oswestry Disability Index at 12 months. Other outcomes included the Oswestry Disability Index walking item, 6-minute walk test and falls. The economic analyses used the EuroQol EQ-5D-5L to measure quality of life. Results Among Oxford Pain Activity and Lifestyle participants, 34% (1786/5304) reported back pain. A further 19.5% (1035/5304) reported back pain and associated leg pain, with 11.2% (n = 594/5304) reporting symptoms consistent with neurogenic claudication. Participants with back pain had worse quality of life compared to those without back pain and reported more adverse health states such as falls, frailty, low walking confidence and mobility decline. Those with neurogenic claudication were worst affected. At 2 years' follow-up, among those reporting back pain at baseline, only 23% (489/2100) no longer reported symptoms. Recovery was lowest among participants reporting neurogenic claudication at baseline, with 90% still reporting symptoms. At 2 years' follow-up, 18.6% of Oxford Pain Activity and Lifestyle participants reported mobility decline. Back pain with/without leg pain was not an independent predictor of mobility decline, but lower limb pain and the report of severe pain were independent predictors. Other predictors included slow walking pace, balance difficulties, low walking confidence, walking ability worse than last year, self-reported general health and comorbidity. In the Better Outcomes for Older people with Spinal Trouble trial, there was no significant difference in Oswestry Disability Index scores between treatment groups at 12 months (adjusted mean difference −1.4, 95% confidence interval −4.03 to 1.17), but at 6 months, scores favoured the Better Outcomes for Older people with Spinal Trouble programme (adjusted mean difference −3.7, 95% confidence interval −6.27 to −1.06). The Better Outcomes for Older people with Spinal Trouble programme resulted in greater improvements in the 6-minute walk test (mean difference 21.7 m, 95% confidence interval 5.96 to 37.38 m) and walking item (mean difference −0.2, 95% confidence interval −0.45 to −0.01) and reduced falls risk (odds ratio 0.6, 95% confidence interval 0.40 to 0.98) compared to best practice advice at 12 months. The probability that the Better Outcomes for Older people with Spinal Trouble programme is cost-effective ranged between 67% and 83% (National Health Service and Personal Social Services perspective) and between 79% and 89% (societal perspective) across cost-effectiveness thresholds between £15,000 and £30,000 per quality-adjusted life-year. From the embedded qualitative study, the Better Outcomes for Older people with Spinal Trouble programme was acceptable to participants, and enjoyable. Limitations Many of the data collected were self-reported and thus may be subject to recall bias or may have resulted in misclassification of participants. Conclusions Back pain is a substantial problem for older people, with the majority reporting persistent symptoms. We have developed an effective intervention to improve mobility and reduce falls in older people with neurogenic claudication; however, more effective interventions are needed for back pain generally. We have identified a set of self-reported questions that predict mobility decline in older people, so clinicians and their patients and families know when intervention is needed. Future work Develop and evaluate treatments for older people with back pain. Optimisation of the Better Outcomes for Older people with Spinal Trouble programme to better target pain-related disability. External validation of the Oxford Pain Activity and Lifestyle prognostic tool. Study registration This trial is registered as BOOST trial ISRCTN12698674. Funding This award was funded by the National Institute for Health and Care Research (NIHR) Programme Grants for Applied Research programme (NIHR award ref: PTC-RP-PG-0213-20002) and is published in full in Programme Grants for Applied Research; Vol. 11, No. 9. See the NIHR Funding and Awards website for further award information. Plain language summary Back pain is a common problem for older people. This research aimed to increase our understanding of back pain in older people and to develop treatments to reduce the burden caused by back pain. The research was arranged in six work packages, and we completed three linked studies. Study 1: We enrolled 5409 older people in a cohort study. Participants answered questions about back pain, their health, mobility, falls and quality of life on enrolment and at 1 and 2 years' follow-up. Back pain was reported by half of the participants, and 20% also reported leg pain. Back pain with/without leg pain is associated with reduced quality of life but also with being frail, falling and having walking problems. After 2 years, 77% of participants still reported being troubled by this pain. We developed a tool to identify when older people were at risk of reduced walking ability and to understand whether back pain was important here. Back and leg pain were not specifically linked to reduced walking, but severe pain was, suggesting that regardless of the type of pain, it needs to be treated. This tool could be used by clinicians and patients to know when they are at risk of reduced walking ability and to seek treatment. Study 2: We developed a group physiotherapy programme (the Better Outcomes for Older people with Spinal Trouble programme) for older people with a back-related condition called neurogenic claudication which results in pain spreading from the back into the legs and difficulties standing and walking. We tested the programme in a randomised controlled trial. The Better Outcomes for Older people with Spinal Trouble programme resulted in long-term improvements in walking, reduced falls, and short-term improvements in pain and disability. It is likely to be good value for the National Health Service. Study 3: We interviewed participants taking part in the Better Outcomes for Older people with Spinal Trouble trial to understand their experiences of the trial and whether the treatments helped.